(untitled) (Journal of the American Pomological Society, 1964)
Fruit growers, nurserymen and scientists met in mid-September to celebrate the spur-type ’Starkspur Golden Delicious’ recently introduced by Stark Bros. Nursery. It was the second such celebration held in recent years. About two years ago a similar group met at Hood River, Oregon, to honor ’Starkrimson’, a new spur type of the ’Red Delicious’.